1 Review of the Identification and Management of Contractures in Inpatients with Dementia In A District General Hospital. (6th February 2020) - Burns, R; Wightman, R; Mon, H; Robertson, A
Abstract: Background: Patients with dementia are at risk of contractures which are associated with pain, pressure sores, increased carer burden and reduced function (1). It has been estimated up to 55% of residents in nursing homes have a contracture (2). Locally, patients are identified and treated in care homes. We questioned why comparatively few hospital inpatients were seen. Methods: We audited acute elderly inpatients at a large district general hospital on two days. Patients with a diagnosis of dementia were identified and then checked for contractures. Information was collected on a proforma. Patients audited on day one were excluded from day two. Results: 410 patients were audited. 100 patients were identified with dementia. 21 individual contractures were identified with the hands been the most common site (47.6%). Only three contractures had been highlighted in the medical notes. Patients with contractures were more likely to be at home with carers or in a care facility (93.7% verse 64.3%). None of the patients with contractures were independently mobile. Higher proportions (31.2% vs 8.3%) with contractures were bedbound compared to those without. Complications were identified, with two patients reporting pain and three patients having pressure sores. Only one patient was receiving treatment for their contractures. Patients with contractures were more likely to have a higher frailty score, had a previous stroke (37.5% verse 13.1%) and have a vascular type dementia (31.3% verse 14.2%). Conclusions: Contractures were a significant problem in our inpatient population in patients with a diagnosis of dementia. A large proportion were not identified by the clerking team, not receiving treatment and beginning to have complications. Subsequently a presentation highlighting this issue was carried out to junior doctors on the elderly wards, a coding proforma for contractures was produced and a guide to management of this issue is being put together for use in the inpatient setting. References: 1. Souren L, Franssen, Reisberg E. Contractures and loss of function in patients with Alzheimer's disease, J. Am. Geriatr. Soc. 1995; 43(6): 650–655. 2. Offenbacher M, Sauer S, Riess J, Muller M, et al. Disabil Rehabil 2013; 36(7): 529–538.